Serum Copper And Serum Ceruloplasmin Levels In Acute Myocarial Infarctionv - G.VENKATARAMANA; V.KRISHNAMURTHY; V.ANJANEYA PRASAD (International Journal of Pharma and Bio Sciences, 2012)
Copper, a strong prooxidant, may play a role in atherogenesis. Serum Cu and caeruloplasmin levels have been suggested to be independent risk factors for coronary heart disease operating through oxidative modification of low density lipoprotein. Fifty cases of Acute Myocardial Iinfarction and fifty age and sex-matched controls were recruited. Copper and ceruloplasmin levels were estimated in controls and in cases at the time of diagnosis and weekly In cases copper and ceruloplasmin levels were statistically significantly elevated (p <0.0001) compared to controls. And Serum copper and ceruloplasmin levels were maximum on 7th day of infarction, gradually declining from 7th to 28th day of infarction to normal ranges (P value is 0.0001). This suggests that serum copper and ceruloplasmin levels decreased in cases with institution of treatment.